Development of novel microsatellite markers using RAD sequencing technology for diversity assessment of rambutan (Nephelium lappaceum L.) germplasm - Shahril Ab Razak; Salehudin Mad Radzuan; Norkhairi Mohamed; Nor Helwa Ezzah Nor Azman; Alny Marlynni Abd Majid; Siti Norhayati Ismail; Muhammad Fairuz Mohd Yusof; Johari Sarip; Khairun Hisam Nasir (Heliyon, 2020)
The trend of microsatellite marker discovery and development revolved as a result of the advancement of next generation sequencing (NGS) technology as it has developed numerous microsatellites within a short period of time at a low cost. This study generated microsatellite markers using RAD sequencing technologies for the understudied Nephelium lappaceum. A total of 1403 microsatellite markers were successfully designed, which consisted of 853 di-, 525 tri-, 17 tetra-, 5 penta-, and 3 hexanucleotide microsatellite markers. Subsequently, selection of 39 microsatellites was made for the evaluation of genetic diversity of the selected 22 rambutan varieties. Twelve microsatellites, which exhibited high call rates across the samples, were used to assess the diversity of the aforementioned rambutan varieties. The analysis of 12 microsatellites revealed the presence of 72 alleles and six alleles per locus in average. Furthermore, the polymorphic information content (PIC) value ranged from 0.326 (NlaSSR20) to 0.832 (NlaSSR32), which included an average of 0.629 per locus, while the generated Neighbour Joining dendrogram showed two major clusters. The pairwise genetic distance of shared alleles exhibited a range of values from 0.046 (R134↔R170) to 0.818 (R5↔R170), which suggested highest dissimilarity detected between R5 and R170. Notably, these research findings would useful for varietal identification, proper management and conservation of the genetic resources, and exploitation and utilization in future breeding programs.